Bile duct injury complications and management - Bhuiyan, Jahangir Hossain; Khan, MA Wahab; Rabbi, ANM Atai; Akhter, Latifa (Journal of Armed Forces Medical College, Bangladesh, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> doi:10.3329/jafmc.v4i2.1840 JAFMC Bangladesh Vol.4(2) 2008 21-26